Pelatihan UMKM Dalam Menghadapi Tantangan Pemasaran di Era Digital: Studi Kasus UMKM Desa Sepulu, Kecamatan Sepulu, Kabupaten Bangkalan - Sultan Syah; Afiful Asrofi; Ade Rizaldi Hidayatullah (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
The UMKM training in Sepulu Village, Bangkalan aims to enhance entrepreneurs' abilities to tackle marketing challenges in the digital era. Challenges such as low digital literacy, limited access to technology, and underutilization of digital platforms are major obstacles for UMKM. This study adopts a participatory, need-based approach, encompassing needs analysis, program design, implementation, and post-training evaluation. The training materials cover digital marketing introduction, strategies for using social media and e-commerce, and creative content creation. The results show improved participants' understanding of digital marketing and their ability to leverage technology to expand markets and boost sales. This training is expected to drive UMKM growth, foster relevant marketing innovations, and positively impact the local economy.